The Study Quenching Process on Rubber Tapping Knives Home Industry Production - Indra Gunawan; Yahya; Firdaus (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The rubber tapping knives produced by blacksmiths have cracks and chipped and even broken on their blades, so rubber farmers must often replace them with new knives. Thus the product cannot be used for a long time and has reduced economic value. The cause of this rubber tapping knives made by blacksmiths is easily damaged because the gilding method on the product is not done properly. So the product was produced have a relatively low level of hardness. This study aims to determine the effect of the hardening and quenching process on the hardness of rubber tapping knives made by blacksmiths. Data of test were analyzed using ANOVA with full factorial level design, main effect model design, and 3 replications assisted with Design-Expert software. At a temperature of 800℃, the maximum hardness value of 62,8 HRC obtained from the quenching results using a water cooling media, while the minimum hardness value of 62,2 HRC was obtained from oil cooling media. At a temperature of 850℃ the maximum hardness value of 60,4 HRC obtained from the quenching results using water cooling media, and the minimum hardness value obtained from the oil cooling media is 59,1 HRC.